Influence of Thermal and Radiation Effects on the Phase Composition, Structure and Stress-Strain State of Ti-W-B System Coatings Deposited from Ion-atomic Fluxes - O.A. Shovkoplyas; O.V. Sobol (Журнал нано- та електронної фізики)
The regularities of the formation of ion-plasma coatings of Ti‑W‑B system and the impact of postcondensation treatment on their phase composition, structure, substructure and stress state. It is shown that at a low content of Ti‑component (up to 2 at.% ) two-phase state from β‑WB‑ and (Ti, W)B2‑ phases is formed. Annealing at 1270 K leads to the grain growth of the β‑WB‑phase mainly. When the content of Ti is more than 5 at.%, a single-phase (Ti, W)B2 state of the coating is formed. Structure and substructural characteristics of these coatings are stable at annealing and proton irradiation with the energy of 200 keV up to the dose of 6,5×1017 cm–2. Influence of thermal-radiation exposure affects the change of the stress-strain state (relaxation of compressive strain). The observed changes are explained on the basis of minimizing the free energy of the system.